2012
DOI: 10.25336/p6731k
|View full text |Cite
|
Sign up to set email alerts
|

Proximate determinants of declining fertility in Oman in the 1990s

Abstract: The current fertility rate in Oman declined dramatically from a very high rate of 8.6 births per woman in 1988 to 4.8 births per woman in 2000, a decline of nearly four births per woman or a decline of 44 per cent of total fertility over a period of twelve years. This decline has occurred in the absence of any official national level family planning programme. Using recent national level survey data and the Bongaarts framework of the proximate determinants of fertility, in this study an attempt has been made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…Multiplying all of the indices together by the total fecundity rate of 15.3 produces the predicted TFR for the population. The predicted TFR typically differs from the observed TFR because of underreporting of births, measurement errors of the proximate determinants, or the omission of any other potential proximate determinants that are influential in determining fertility levels in that particular population under study (Islam et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiplying all of the indices together by the total fecundity rate of 15.3 produces the predicted TFR for the population. The predicted TFR typically differs from the observed TFR because of underreporting of births, measurement errors of the proximate determinants, or the omission of any other potential proximate determinants that are influential in determining fertility levels in that particular population under study (Islam et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Bongaarts (1978) in his classical paper termed these biological and behavioral factors as proximate determinants of fertility, since they directly affect fertility; and all other social, economic and environmental factors affect fertility through these factors. As these proximate determinants are well recognized for explaining aggregate fertility level, many researches exist till now for Bangladesh along with others developing and developed countries (Kabir and Uddin 1987, Islam et al 1998, Islam et al 2011, Rabbi and Kabir 2014. However, most of these approaches overlooked policy proposition regarding others proximate determinants; those also have précised influence on fertility decline.…”
Section: Rabbimentioning
confidence: 99%
“…Multiplying all the indices together by the total fecundity rate of 15.3 produces the predicted TFR for the population. The predicted TFR typically differs from the observed TFR because of underreporting of births, measurement errors of the proximate determinants, or the omission of any other potential proximate determinants that are influential in determining fertility levels in that population under study (Islam et al 2011).…”
Section: Role Of Major Proximate Determinants In Fertility Declinementioning
confidence: 99%
“…As these proximate determinants are well recognized for explaining aggregate fertility level, many researches exist till now for Bangladesh along with other developing and developed countries (Rabbi 2015;Islam et al 2011;Mahjabeen and Khan 2011;Erfani and McQuillan 2008;Kabir and Chowdhury 2004;Islam et al 1998, Islam andIslam 1993;Kabir and Uddin 1987;Wang et al 1987). Most of these studies are done to explain current fertility level of specific country or countries, though many of them estimated the required level of contraceptive prevalence rate to achieve replacement level of fertility (Mahjabeen and Khan 2011).…”
Section: Figure 2 Fertility Trend Inmentioning
confidence: 99%
“…The reduction in the opportunity cost of time devoted to children (forgone wages) associated with an unemployment spell is expected to boost fertility [8]. Another study revealed that women education and employment are likely factors that encourage couples to delay marriage and use modern family planning methods which play vital role in reducing marital fertility in Oman [9]. It is also observed that, if the negative income effect from reduced work earnings is sufficiently large, unemployment may lead to increase in fertility level.…”
Section: Introductionmentioning
confidence: 99%